Prevalence of overweight and obesity in elderly people from Vitória-ES, Brazil - Andrade,Fabíola Bof de (2012)
The scope of this study was to estimate the prevalence of overweight and obesity and its association with socio-economic status in a sample of non-institutionalized elderly people from Vitória-ES, Brazil. This was a cross-sectional survey with a sample of 882 elderly people aged 60 and over. Obesity and overweight were assessed using the body mass index (BMI) and waist circumference (WC). All subjects answered a personal and socio-demographic questionnaire in relation to age, gender, marital status, physical activity, number of children, chronic diseases and smoking. Associations between categorical variables were tested using chi-square analysis with a 5% significance level. The prevalence of overweight and obesity was high (41.8% and 23.4%, respectively) and 50.7% of the elderly had a substantially increased waist circumference. About 4.3% of the individuals had diabetes, 50.4% had hypertension and 14.9% were found to have both diseases. It was observed that both the BMI and WC were significant associated (p<0.05) with sex, marital status, the presence of diseases and with cigarette smoking.